2013
DOI: 10.1029/2012gm001322
|View full text |Cite
|
Sign up to set email alerts
|

Large-Amplitude Whistler Waves and Electron Acceleration in the Earth's Radiation Belts: A Review of Stereo and Wind Observations

Abstract: One of the critical problems for understanding the dynamics of Earth's radiation belts is determining the physical processes that energize and scatter relativistic electrons. We review measurements from the Wind/Waves and STEREO S/Waves waveform capture instruments of large amplitude whistler-mode waves. These observations have provided strong evidence that large amplitude (100s mV/m) whistlermode waves are common during magnetically active periods. The large amplitude whistlers have characteristics that are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…13 of 70 The peak-to-peak electric and magnetic field amplitudes of whistler mode waves can exceed 200 mV/m and 8 nT, respectively (Kellogg et al, 2011;Wilson et al, 2011). These values are >10 times the magnitude of previous observations and call into question the assumptions required in quasi-linear diffusion models that are based upon much smaller wave amplitudes (e.g., see review by Cattell et al, 2012). For each magnetospheric pass examined that traversed the radiation belts, Wilson et al (2011) found that large amplitude waves were present in the radiation belts.…”
Section: The Radiation Beltsmentioning
confidence: 98%
See 1 more Smart Citation
“…13 of 70 The peak-to-peak electric and magnetic field amplitudes of whistler mode waves can exceed 200 mV/m and 8 nT, respectively (Kellogg et al, 2011;Wilson et al, 2011). These values are >10 times the magnitude of previous observations and call into question the assumptions required in quasi-linear diffusion models that are based upon much smaller wave amplitudes (e.g., see review by Cattell et al, 2012). For each magnetospheric pass examined that traversed the radiation belts, Wilson et al (2011) found that large amplitude waves were present in the radiation belts.…”
Section: The Radiation Beltsmentioning
confidence: 98%
“…Wind studies of large amplitude whistler waves in the terrestrial radiation belts (Kellogg et al, 2011;Kersten et al, 2011;Wilson III et al, 2011) have led to a series of new theoretical analyses based upon the new, much larger wave amplitude estimates (note these were originally discovered by Cattell et al, 2008, using STEREO observations). A comprehensive review of large amplitude whistler mode waves in the radiation belts can be found in the review by Cattell et al (2012). Whistler mode waves are right-hand polarized (with respect to quasi-static magnetic field), electromagnetic emissions that are found in virtually all regions of space (e.g., see discussions in Cattell et al, 2012;Wilson, Koval, Szabo, et al, 2013, and references therein).…”
Section: The Radiation Beltsmentioning
confidence: 99%
“…Strong nonlinear scattering is known to occur with large amplitude whistler mode waves (Albert, 2002;Cattell et al, 2008Cattell et al, , 2012Tao et al, 2012). Inferred chorus amplitudes are up to ∌900 pT and ∌15 mV/m.…”
Section: Resonance Location and Mechanismmentioning
confidence: 99%
“…Electromagnetic whistler mode waves have long been among the most commonly observed and studied space plasma emissions (see, e.g., Burtis & Helliwell, 1969;Taylor & Gurnett, 1968). Within the Earth's magnetosphere, whistler mode waves are typically observed as either broadband hiss found inside the plasmasphere and in plumes (Hartley et al, 2018;Malaspina et al, 2016Malaspina et al, , 2018Meredith et al, 2006;Thorne et al, 1973), or discrete emissions observed outside the plasmapause known as chorus waves (Li et al, 2009(Li et al, , 2016Tsurutani & Smith, 1977), occasionally at very large amplitudes in the radiation belts (Cattell et al, 2008(Cattell et al, , 2012. These chorus waves typically (but not always; Kurita et al, 2012) occur in two bands separated by a gap at half the equatorial electron cyclotron frequency f ce and are often observed as discrete rising (increasing in frequency with time) or falling (decreasing) tones lasting a few tenths of a second.…”
Section: Introduction/backgroundmentioning
confidence: 99%